La prostitución en el corazón del capitalismo - Ranea Triviño, Beatriz (Investigaciones Feministas, 2018)
Reseña:  Rosa Cobo, Editorial Los Libros de la La Catarata, Madrid, 2017, 213 páginas. ISBN: 978-84-9097-326-4